Pharmacological Evaluation of Najas gracillima from the Bay of Bengal Coastal Regions: In Vitro and In Silico Studies - Hossen, S. M. Moazzem; Wahiduzzaman, Mohammad; Kader, Md Anower; Chowdhury, Sajjad Hossen; Mamun, Md Al; Hafiz, Md Al; Begum, Ayesha; Ali, Md. Liakot; Meem, Jannatul Naima; Jalil, Muhammad Abdul; Hoque, Neamul; Hamid, Mohammad Forkanul (Iraqi Journal of Science, 2025)
Najas gracillima is a green seaweed commonly found in North America and East Asia. This study explored its phytochemical composition and assessed its antioxidant activity using 2,2-diphenyl-1-picrylhydrazyl (DPPH) and 2,2′-azino-bis(3-ethylbenzothiazoline-6-sulfonic acid) (ABTS) assays, along with α-amylase inhibition and cytotoxicity evaluations via the brine shrimp lethality bioassay (BSLB) and the HeLa cancer cell line. The acetone extract of Najas gracillima (ANG) showed a total phenolic content of 14.26 ± 1.86 mg GAE/g extract and a total flavonoid content of 10.27 ± 2.24 mg QUE/g extract. ANG demonstrated strong antioxidant activity (IC₅₀ for DPPH: 14.57 ± 0.93 µg/mL; IC₅₀ for ABTS: 32.17 ± 1.35 µg/mL) and moderate α-amylase inhibition (IC₅₀: 54.97 ± 3.36 µg/mL). While it showed mild cytotoxicity in the BSLB assay (LC₅₀: 673.08 μg/mL), no cytotoxic effects were observed against HeLa cells. Molecular docking analysis revealed that the identified compounds exhibited strong binding affinities to relevant drug target proteins associated with the observed biological activities. These findings suggest that N. gracillima may serve as a valuable source of bioactive compounds with potential applications in managing oxidative stress and diabetes.